Study of Pulsed Light-Induced Damage on Saccharomyces cerevisiae in Apple Juice by Flow Cytometry and Transmission Electron Microscopy - Ferrario, Mariana Inés (2014)
This work analyzed the pulsed light (PL) (0.0-71.6 J/cm2)-induced damage on Saccharomyces cerevisiae KE162 cells in peptone water (pH 3.5 or 5.6) and apple juice (pH 3.5) by applying flow cytometry (FCM) and transmission electronic microscopy. Cells were labeled with fluorescein diacetate (FDA) for detecting membrane integrity and esterase activity and with propidium iodide (PI) for monitoring membrane integrity. S. cerevisiae inactivation curves reached 6-7 log reductions (peptone water systems) and 3.9 log reductions (apple juice) after 60 s (71.6 J/cm2) of PL exposure. FCM revealed the same damage pattern (although at different doses) in all media: at low doses, there was an increase in population in PI+-FDA+ quadrant, while at high doses, most of the population was located at quadrant PI+-FDA-, indicating that PL provoked rupture of the cytoplasm membrane allowing PI to penetrate cells and there was progressive loss of esterase activity. Comparison of conventional culture technique with FCM revealed the occurrence of certain cell subpopulations in peptone water with pH 3.5 which were stressed and lost their ability to grow in agar but still showed metabolic activity. Transmission electron microphotographs of PL-treated cells clearly indicated that various cell structures other than plasma membranes were altered and/or destroyed in a different degree depending on exposure time and type of medium.